Platelets and diseases: signal transduction and advances in targeted therapy - Yuchen Tian; Yao Zong; Yidan Pang; Zhikai Zheng; Yiyang Ma; Changqing Zhang; Junjie Gao (Signal Transduction and Targeted Therapy)
Abstract Platelets are essential anucleate blood cells that play pivotal roles in hemostasis, tissue repair, and immune modulation. Originating from megakaryocytes in the bone marrow, platelets are small in size but possess a highly specialized structure that enables them to execute a wide range of physiological functions. The platelet cytoplasm is enriched with functional proteins, organelles, and granules that facilitate their activation and participation in tissue repair processes. Platelet membranes are densely populated with a variety of receptors, which, upon activation, initiate complex intracellular signaling cascades. These signaling pathways govern platelet activation, aggregation, and the release of bioactive molecules, including growth factors, cytokines, and chemokines. Through these mechanisms, platelets are integral to critical physiological processes such as thrombosis, wound healing, and immune surveillance. However, dysregulated platelet function can contribute to pathological conditions, including cancer metastasis, atherosclerosis, and chronic inflammation. Due to their central involvement in both normal physiology and disease, platelets have become prominent targets for therapeutic intervention. Current treatments primarily aim to modulate platelet signaling to prevent thrombosis in cardiovascular diseases or to reduce excessive platelet aggregation in other pathological conditions. Antiplatelet therapies are widely employed in clinical practice to mitigate clot formation in high-risk patients. As platelet biology continues to evolve, emerging therapeutic strategies focus on refining platelet modulation to enhance clinical outcomes and prevent complications associated with platelet dysfunction. This review explores the structure, signaling pathways, biological functions, and therapeutic potential of platelets, highlighting their roles in both physiological and pathological contexts.